Pelatihan Pembuatan Air Ragi Salak (Salacca Zalacca) Dan Roti Di Desa Wisata Ledoknongko - Khumaira, Annisa; Sandra Fitriany, Dhea; Annaziha, Salma; Zintya Sari, Fitria; Mindrati Fardhani, Dinar (Universitas Muhammadiyah Malang, 2023)
Salak (Salacca zalacca) is a fruit that is widely developed in Sleman, Yogyakarta Special Region, and as an icon of the Ledoknongko Tourism Village. The Covid-19 pandemic has reduced the number of tourists visiting the Ledoknongko Tourism Village. Covid-19 is very influential on residents' income and, of course, the use of salak fruit. One alternative to using salak fruit is to process it into natural yeast made from salak fruit (Salak Yeast Water). Natural yeast or wild yeast is the yeast that is usually always present in some foods, such as fruits, vegetables, and cereals. Furthermore, the yeast can be used for making bread. The training was conducted for a group of women from the Ledoknongko Tourism Village, which included a pre-test, giving materials, the practice of making salak yeast and fried bread, and a post-test. The pre-test and post-test results showed the participant's understanding of salak yeast; in the pre-test, the correct answers were 30%, and in the post-test, 93%. In addition, according to a survey conducted, particpants have a high desire to continue to train skills and develop products from salak yeast water so that salak yeast water has the potential to continue to be developed and commercialized in Ledokonongko Tourism Village